Dissecting the roles and clinical potential of YY1 in the tumor microenvironment - Li, MengNa; Wei, JianXia; Xue, ChangNing; Zhou, XiangTing; Chen, ShiPeng; Zheng, LeMei; Duan, YuMei; Deng, HongYu; Xiong, Wei; Tang, FaQing; Li, GuiYuan; Zhou, Ming (Frontiers in Oncology, 2023)
Yin Yang 1 (YY1), a member of the GLI-Kruppel family of zinc finger proteins, plays a dual biological role as an oncogene or a tumor suppressor during tumorigenesis and tumor progression. The tumor microenvironment (TME) is recognized as the “soil” of cancer that plays a critical role in tumor growth and metastasis. Recent studies have shown that YY1 is closely related to the remodeling and regulation of the TME. Herein, we reviewed the expression pattern of YY1 in tumors and its correlation with clinical progression and prognosis and summarized the function and mechanism of YY1 in regulating tumor angiogenesis, metabolism, and the immune microenvironment. In addition, we discussed the potential value of YY1 in tumor diagnosis and treatment and provided a new molecular strategy for the clinical diagnosis and treatment of tumors.